Industrial Clusters In Biotechnology : Driving Forces, Development Processes And Management Practices. - Chiesa, Vittorio (World Scientific, 2004)
This book presents the results of Cleverbio, a project funded by theEuropean Commission. The project examined the process of growth anddevelopment of clusters in the biotech industry, identifying andstudying the main driving forces. The empirical work involved in-depthanalysis of five clusters at different stages of development:Cambridge, the most important cluster in Europe; Heidelberg, one ofthe strongest in Germany; Aarhus in Denmark; Marseille in France; andMilano in Italy at an early stage of development.